Determinants of population growth in Pakistan - Shams ul Huda (International Journal of Endorsing Health Science Research, 2014)
Population growth is a major problem of developing countries, which adversely affect economic growth and development. Today world population is 7.2 billion almost double of 1960 population. Pakistan is the 6th populous country with population of 188.2 million. Population growth in Pakistan is 1.95 almost double of world population growth. Unplanned population growth results in severe shortage of resources, increase food insecurities and threaten health care system of Pakistan. Moreover, Infrastructures, roads, water and sanitation systems are deficient to meet the necessities of growing population. There are several factors which contribute in population growth including high fertility rate, inadequate family planning practices, and low income. Illiteracy, lack of political well, inefficient bureaucracy, cultural and religious back ground also has profound effect on population growth.